Sustainable infrastructure provision through awareness in selected medium-sized towns in Kwara State - Afolayan Ganiyu Popoola; Tunde Afolabi Monisola (Bulletin of Geography. Socio-Economic Series)
Infrastructure is a basic structure required for sustainable socio-economic and physical development of any human settlement. The issue of sustainable development has recently been linked to infrastructure sustainability. Required to achieve this is the acquisition of appropriate education. Different skills, understanding the complexities that threaten the survival of our system, critical and systematic thinking, building capacity and partnership in decision-making, which are essential tools for Education for Sustainable Development (ESD), are required to provide adequate, appropriate and functional infrastructure. This study therefore examines the awareness/knowledge with reference to various skills employed in the provision of infrastructure through communal efforts in ten selected medium-sized towns in Kwara State. These towns are with a population of between 5,000 and 20,000. A total of 400 household heads were sampled systematically through the administration of a questionnaire in the ten selected medium-sized towns. Tabulations, cross tabulations, percentages and chi-square analysis were employed to analyse the gathered data. The findings revealed a significant relationship between awareness/knowledge and the provision of infrastructure with a calculated value of 219.23 greater than the tabulated value 34.41 at alpha level 0.05. Indigenous knowledge coupled with the ideas brought home by indigenes that have travelled far from their immediate communities and some professional skills acquired through community participation in infrastructure provision were employed to provide basic infrastructure required for socio-economic and physical development. Among the infrastructure provided are water, roads, health centres and electricity. The study recommends the improvement of basic education, a review and re-orientation of our educational system to address sustainability for proper collaboration of community efforts with the Community Development division of various local governments. This could be through training of the local communities and promotion of partnership zeal with Non-Governmental Organizations (NGOs) in infrastructure provision.